HIV Knowledge and Risk Behaviours of Junior Staff of the University of Ibadan, Nigeria (2015)
Human Immunodeficiency Virus (HIV) infection remains a public health challenge and Nigerian universities are not immune to the effect of the epidemic. Despite the fact that non academic junior staff constitute a significant proportion of the workforce and are at risk due to their lower level of education and socio-economic status, few studies have focused on them. The broad aim of this study is to assess the HIV knowledge, risk perception and behaviours of junior staff of the University of Ibadan, Nigeria. A cross-sectional study was conducted among 700 junior staff of the University of Ibadan. Respondents were selected using multistage sampling technique and completed structured interviewer-administered questionnaires. The quantitative data was analyzed using the Statistical Package for the Social Sciences (version 17) to generate frequencies and cross tabulations of The mean age of the respondents was 38.89.9 years, 74.6% were males, 76.4% were married and 51.6% had post secondary education. Majority identified blood transfusion 94.4% and sexual intercourse 97.3% as the main routes of transmission. The commonest methods of prevention known were condom use 79.6% and mutual fidelity 89.7%. Respondents aged 20-29 years, the single and those with post-secondary education (P=0.000) had higher HIV related knowledge. Only10% of the respondents perceived that they were at risk of contracting the disease; 30.3% did not think People Living with HIV and AIDS (PLWHAs) should continue to work. Fifteen percent reported sexual intercourse with a non-regular partner in the previous 12 months and 30.8% of this group did not use a condom. Workplace health education programmes to reduce HIV risk behaviours and stigmatizing attitudes are recommended .variables.